15-Year Secular Trends in Cognitive Function Among Older Adults in the United States. Issue 3 (June 2019) - Frith, Emily; Loprinzi, Paul D.
Cognitive impairment is associated with various chronic diseases, including mobility limitation and early mortality. Thus, evaluating changes in cognition is of paramount public health interest. The purpose of this study was to evaluate secular trends in cognitive function among a representative sample of the U.S. older adult population. Data from the 1999–2000, 2001–2002, 2011–2012, and 2013–2014 National Health and Nutrition Examination Survey were utilized to identify an aggregate sample of adults 60+ years of age. The sample size across the four respective cycles was 1417, 1558, 1422, and 1592. Three cognitive assessments were employed, including the CERAD Word Learning subset (Consortium to Establish a Registry for Alzheimer's disease), the Animal Fluency test, and the Digit Symbol Substitution Test (DSST). For the entire sample and several subpopulations, DSST scores increased from 1999 to 2012 and then decreased in the 2013 to 2014 cycle. For all CERAD trials, there was evidence of increased CERAD performance from 2011–2012 to 2013–2014. No secular trends were observed for the Animal Fluency task across these cycles. Select cognitive parameters appear to be improving among U.S. older adults. Future work is needed to further explore secular trends in cognitive sustainability, and, as evidenced by our present study, cognitive enrichment over time.